Ultrasound-Guided Measurement of Piriformis Muscle Thickness to Diagnose Piriformis Syndrome - Siahaan, Yusak Mangara Tua; Tiffani, Pamela; Tanasia, Amanda (Frontiers in Neurology, 2021)
Piriformis syndrome (PS) is a neuromuscular condition due to the entrapment of sciatic nerve at the level of piriformis muscle (PM). Diagnosing PS remain challenging despite recent invasive and non-invasive diagnostic method. Response to invasive nerve block is still one of the most reliable diagnostic modalities because there is no gold standard test for PS. As early diagnosis would prevent delayed diagnosis that results in chronic somatic dysfunction and muscle weakness, a screening test with high sensitivity could guide clinicians to make the next appropriate step in diagnosing PS. Aim To determine sensitivity, specificity, best cut-off point of ultrasound-guided PM thickness in PS Method This case control study was conducted in general hospital in Tangerang during a-3-month period. We recruited 58 clinically diagnosed PS and 58 healthy patients (without history of hip and buttock pain) during their visits in the outpatient clinic. All patients underwent assessment by ultrasound to measure the thickness of bilateral PM. Gender, age, body mass index, history of micro-/macro-trauma and prolonged sitting duration were recorded. Statistical analysis was performed using SPSS version 25. Result PS and control groups were dominated by female, with mean age of 51.79±14.10 years on PS subjects and 50.09±13.26 years on healthy subjects. The ultrasound-guided PM thickness were increased in PS patients compared to healthy subjects with mean 1.16±0.13 and 0,85±0.11 respectively (p value <0.05). The area under receiver operating characteristic curve (AUROC) of PM was 0.970 (95% confidence interval [CI] 0.943-0.998; p value <0.05). The best cut-off point defined by Youden’s J index was 0.9950 cm for all PS subjects. Conclusion We proposed 0.9950 cm as the cut-off point for diagnosing PS by ultrasound, which has the sensitivity and specificity of 94.8 and 87.9.